THE EFFECT OF GANDASIL D FERTILIZER CONCENTRATION TO GROWTH OF GREEN MUSTARD IN HYDROPONIC - Eko, Eko; Darussalam, Darussalam; Susana, Rini (Jurnal Sains Mahasiswa Pertanian, 2018)
This research aims to determine the best effect of Gandasil D fertilizer on the growth and yield of green mustard plant on hydroponic. The research was conducted at Sungai Raya Village in Sungai Raya District of Kuburaya Regency West Borneo Province. The research was conducted in October 2nd to December 30th 2017. This  research design was Completely  Randomized  Design that consist of 6 treatments with 4 replications. each replication consist of 3 samples, so it’s all totally 72  sample plants. The treatment were p0 (10 ml AB-Mix of water perlitre), p1 (0.2% Gandasil D equal to 2 g of water perlitre), p2 (0.3% Gandasil D equal to 3 g of water perlitre, p3 (0,4% Gandasil D equal to 4 g water perlitre), p4 (0.5% Gandasil D equal to 5 g of water perlitre), p5 (0.6% Gandasil D equal to 6 g water perlitre). The observed parameters were: plant height (cm), number of leaves (leaf), leaf area (cm2), top plant’s fresh weight (g), and top plant’s dry weight (g). The results showed that the concentration of Gandasil D fertilizer had significant effect on plant height, number of leaves, leaf area, top plant’s fresh weight and top plant’s dry weight. Gandasil D fertilizer with concentration of 0,2% was the best does to growth and yield of green mustard.